PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN BELLAGIO RESTAURANT DI GRAND JATRA HOTEL PEKANBARU - Pratama, Agung Adhya; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to understand if all five service quality dimension (tangible, reliability, assurance, responsiveness and empathy) could affect costumer satisfaction of Bellagio Restaurant at Grand Jatra Hotel Pekanbaru. This research utilize quantitative method to tackle the issue. The population in this research are every hotel guests who visits Bellagio Restaurant, meanwhile the sample in this research consist of 100 respondent. This research uses  questionnaire and observation to accumulate the data with accidental sampling method as data accumulating method. Based on research, results shows three from five service quality dimension (tangible, responsiveness and empathy) have a significant impact towards costumer satisfaction, meanwhile reliability and assurance does not have a significant impact towards costumer satisfaction.  Keywords : Service Quality, Costumer Satisfaction, Restaurant